A General Approach Towards Thermoplastic Multishape‐Memory Polymers via Sequence Structure Design. (26th October 2012) - Luo, Yingwu; Guo, Yunlong; Gao, Xiang; Li, Bo‐Geng; Xie, Tao
<x xml:space="preserve">Abstract</x> The chain sequence of a poly(styrene‐co‐methyl acrylate) copolymer is designed to form a V‐shaped gradient sequence via controlled/living radical emulsion copolymerization. This specially designed chain sequence gives this common copolymer the capacity of multishape memory. The copolymer can sequentially recover to its permanent shape from three or more previously programmed temporary shapes with the stimulus of temperature. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>